2013
DOI: 10.1111/jvp.12053
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based pharmacokinetic model for the prediction of the depletion of methyl‐3‐quinoxaline‐2‐carboxylic acid, the marker residue of olaquindox, in the edible tissues of pigs

Abstract: To estimate the consumer exposure to olaquindox (OLA) residues in porcine edible tissues, a physiologically based pharmacokinetic (PBPK) model for methyl-3-quinoxaline-2-carboxylic acid (MQCA), the marker residue of OLA, was developed in pigs based on the assumptions of the flow-limited distribution, hepatic metabolism, and renal excretion. The model included separate compartments corresponding to blood, muscle, liver, kidney, adipose, and an extra compartment representing the remaining carcass. Physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This may be possibly related to the gradual dilution of antibiotics in the gut, which led to the weakened effects. Pharmacokinetic analysis of olaquindox (Yang B. et al, 2014), oxytetracycline (Mevius et al, 1986), kitasamycin (Sun et al, 2010) showed that all these antibiotics could be absorbed by pig gut after oral administration. The abundances of bacteria such as Clostridium , Bacillus , and Sharpea were consistently decreased in the lumen of stomach, duodenum, and jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…This may be possibly related to the gradual dilution of antibiotics in the gut, which led to the weakened effects. Pharmacokinetic analysis of olaquindox (Yang B. et al, 2014), oxytetracycline (Mevius et al, 1986), kitasamycin (Sun et al, 2010) showed that all these antibiotics could be absorbed by pig gut after oral administration. The abundances of bacteria such as Clostridium , Bacillus , and Sharpea were consistently decreased in the lumen of stomach, duodenum, and jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of predicted (lines) and experimentally determined (points) quinoxaline‐2‐carboxylic acid (QCA) residue concentrations in pig liver, kidney, muscle, and adipose (the chemical‐specific parameters are MQCA values from reference) (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…They were adjusted slightly for better simulating after the values of other specific chemical parameters were ensured. The same method had been used in other report (Yang et al ., ). The partition coefficients of QCA changed scarcely, and the one of CYX was a little higher than the initial value in Table .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, PBPK modeling has been widely used in the area of veterinary medicine, from the prediction of drug tissue residues (Huang et al, ; Leavens et al, ; Yang et al, ), estimating the withdrawal time (Buur, Baynes, Smith, & Riviere, ; Yang, Huang, et al, ; Yang, Zhou, et al, ), to facilitating the food safety assessment (Henri, Carrez, Meda, Laurentie, & Sanders, ; Lin, Gehring, Mochel, Lavé, & Riviere, ; Yang, Huang, et al, ; Yang, Zhou, et al, ). In this study, a PBPK model was established for heavy sows based on a previous generic PBPK model for swine and cattle (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The population PBPK model can be a useful tool to predict the tissue concentrations and withdrawal intervals following extralabel use of veterinary drugs (Henri et al, ; Lin, Gehring, et al, ; Yang, Huang, et al, ; Yang, Yang, et al, ). The current model provides a conservative estimation of extended withdrawal intervals based on all available pharmacokinetic data of penicillin G in heavy sows and significantly extends label‐recommended withdrawal periods.…”
Section: Discussionmentioning
confidence: 99%